A new species of the genus Cheiloceps Uhler, 1895 (Hemiptera: Fulgoromorpha: Issidae) from the Dominican amber - Gnezdilov, Vladimir M.; Sun, Haoran; Perkovsky, Evgeny E. (Zootaxa, 2023)
A new species of the planthopper genus Cheiloceps Uhler, 1895 (Issidae, Issinae, Thioniini), Cheiloceps magnifrons sp. nov., is described from the Dominican amber. Issidae fossils are briefly discussed.